2020
DOI: 10.1177/2325967120921737
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Meniscal Oblique Radial Tears Are Common With ACL Injury: A Classification System Based on Arthroscopic Tear Patterns in 600 Consecutive Patients

Abstract: Background: Meniscal root tears and ramp lesions have been rigorously characterized in recent literature. However, one of the most common lateral meniscal injuries identified with an acute anterior cruciate ligament (ACL) disruption, a posterior horn lateral meniscal oblique radial tear (LMORT), has not been thoroughly described. Purpose: To determine the incidence of all meniscal tears and, more specifically, the incidence of posterior horn LMORTs in a multicenter cohort of consecutive, acute ACL reconstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 26 publications
0
53
0
Order By: Relevance
“…The PACLR LMPRT repair incidence is consistent with findings of prior studies, which have reported 7% to 14% rates of lateral meniscal posterior root injuries concurrent with ACL tears. [9][10][11] However, some of these were imaging-based studies and did not differentiate partial lesions or stable tears that may not need repair as compared with unstable, complete tears that were repaired in our patients. A study by Ahn et al 21 reported a 6.95% incidence of concomitant LMPRTs that required repair at the time of ACLR.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The PACLR LMPRT repair incidence is consistent with findings of prior studies, which have reported 7% to 14% rates of lateral meniscal posterior root injuries concurrent with ACL tears. [9][10][11] However, some of these were imaging-based studies and did not differentiate partial lesions or stable tears that may not need repair as compared with unstable, complete tears that were repaired in our patients. A study by Ahn et al 21 reported a 6.95% incidence of concomitant LMPRTs that required repair at the time of ACLR.…”
Section: Discussionmentioning
confidence: 89%
“…This article was a podium presentation (under the title "Incidence of Lateral Meniscus Root Tears in Revision Versus Primary ACL posterior root tears (LMPRTs) with ACL ruptures. [9][10][11] One study associated male sex and a contact mechanism of injury with LMPRTs in patients with ACL injury. 12 These tears are frequently located within the posterior horn at or near the meniscal root.…”
mentioning
confidence: 99%
“…The radial lateral meniscus tear at the posterior horn is frequently accompanied by an anterior cruciate ligament injury. 4 While the affected leg is placed in a tailor's leg position, an anteromedial portal is created for inserting a hook probe. Then, the radial Fig 1 . A radial tear at the posterior horn of the lateral meniscus in left knee.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Even all-inside meniscal repair techniques with penetrating posterior capsules by suture needles still have a risk of neurovascular injury 3 ; hence, a pure all-inside procedure that keeps the posterior joint capsule intact is adapted as a favorable method at the site. In practice, although all-inside repair procedures at the posterior horn of the lateral meniscus were usually introduced with horizontal sutures techniques, 4 , 5 a horizontal suture is less reliable for maintaining enough reduction in a biomechanical study. 6 Currently, we present a new, simple all-inside lateral meniscal repair technique of the radial tear at the posterior horn that requires no added accessory portal.…”
mentioning
confidence: 99%
“…An all-inside technique is preferred for a LMORT near the root (Fig 4). 7 Postoperative rehabilitation consisted of nonweightbearing for 6 weeks, with range of motion (ROM) limited from 0 to 90 for the first 4 weeks. Return to jogging was typically delayed until 4 to 6 months after surgery, and return to sport was typically achieved at 9 months from surgery.…”
Section: Surgical Techniquementioning
confidence: 99%